Emergency department point-of-care ultrasound diagnosis of submacular hemorrhage presenting as painless loss of vision. Issue 5 (September 2019) - Odom, Mitchell; Herrman, Nicholas W.C.; Huang, Robert; Fung, Christopher; Theyyunni, Nikhil; Cover, Michael
ABSTRACT: Ocular complaints prompt a significant number of emergency department (ED) visits, and they can range from benign to sight-threatening. Detailed fundoscopic examination is difficult, even for experienced providers. Point-of-care ultrasound (POCUS) is increasingly utilized in the ED for numerous applications, including ocular evaluation. We present a case in which ocular POCUS was used to diagnose a submacular hemorrhage in a patient who presented with acute painless loss of vision. Ocular POCUS can be readily employed to assess for myriad clinically significant pathologies. Résumé: Les troubles oculaires motivent un grand nombre de consultations au service des urgences (SU) et peuvent être sans conséquence grave ou, au contraire, entraîner la perte de la vision. Or, l'examen approfondi du fond de l'œil n'est pas chose facile à réaliser, même pour les professionnels de la santé expérimentés. Par ailleurs, on trouve de plus en plus d'applications à l'échographie au chevet (EC), au SU, dont les évaluations oculaires. Ainsi sera exposé dans l'article un cas de perte de vision aiguë et indolore, dans lequel l'EC oculaire a permis de diagnostiquer une hémorragie sous-maculaire. L'examen peut donc se prêter facilement à l'évaluation d'un grand nombre d'affections importantes de l'œil sur le plan clinique.